The nature of development of the education system during the transformation of Indian and Pakistani society - Aldabek, N.A.; Turar, A.S.; Gabdullin, K.T. (Journal of Oriental Studies, 2021)
This article discusses the education systems of India and Pakistan to show that education is a resource that is readily available to some but not to others. The evolution of formal education in India and Pakistan has been strongly influenced by colonial history. Access to education is also strongly influenced by social differences such as religion, caste and gender. The article provides examples of the most significant educational reforms in India and Pakistan. It also explores issues that remain unresolved, such as learning outcomes. The Indian government ultimately recognized education as a fundamental right for a free person in today’s world through the Right to Education Act. India and Pakistan have made significant progress in education and literacy through education development measures. Education is the foundation of the political, social and economic development of any country. India and Pakistan have faced difficult education challenges since their founding as developing countries, so the education system could not be implemented according to the preferences of the nation. This situation was caused by various factors. Experiments to overcome the difficulties inherent in India and Pakistan, which previously lagged significantly in their socio-economic development, were in colonial dependence and experienced serious contradictions in the development of society, are of particular interest in the scientific community. The main purpose of this research work is to compare the problems of the education system in India and Pakistan, based on a critical examination of the available literature, the need and importance of education, we will try to show recommendations for solving the problems of the education system of these two countries. Key words: India, Pakistan, education system, educational problems.